In the shadow of the gallows : race, crime, and American civic identity - DeLombard, Jeannine Marie (Philadelphia : University of Pennsylvania Press, 2012)
"From Puritan Execution Day rituals to gangsta rap, the black criminal has been an enduring presence in American culture. To understand why, Jeannine Marie DeLombard insists, we must set aside the lenses of pathology and persecution and instead view the African American felon from the far more revealing perspectives of publicity and personhood. When the Supreme Court declared in Dred Scott that African Americans have "no rights which the white man was bound to respect," it overlooked the right to due process, which ensured that black offenders - even slaves - appeared as persons in the eyes of the law. In the familiar account of African Americans' historical shift "from plantation to prison," we have forgotten how, for a century before the Civil War, state punishment affirmed black political membership in the breach, while a thriving popular crime literature provided early America's best-known models of individual black selfhood. Before there was the slave narrative, there was the criminal confession. Placing the black condemned at the forefront of the African American canon allows us to see how a later generation of enslaved activists - most notably, Frederick Douglass - could marshal the public presence and civic authority necessary to fashion themselves as eligible citizens. At the same time, in an era when abolitionists were charging Americans with the national crime of "manstealing," a racialized sense of culpability became equally central to white civic identity. What, for African Americans, is the legacy of a citizenship grounded in culpable personhood? For white Americans, must membership in a nation built on race slavery always betoken guilt? In the Shadow of the Gallows reads classics by J. Hector St. John de Crévecoeur, Edgar Allan Poe, Frederick Douglass, Herman Melville, George Lippard, and Edward Everett Hale alongside execution sermons, criminal confessions, trial transcripts, philosophical treatises, and political polemics to address fundamental questions about race, responsibility, and American civic belonging."--Project Muse.
Introduction: How a slave was made a man -- Part I. Contracting guilt : mixed character, civil slavery, and the social compact ; Black catalogues : crime, print, and the rise of the black self -- Part II. The ignominious cord : crime, counterfactuals, and the new black politics ; The work of death : time, crime, and personhood in Jacksonian America ; How freeman was made a madman : race, capacity, and citizenship ; Who aint a slaver? Citizenship, piracy, and slaver narratives -- Conclusion.
Includes bibliographical references and index.
Print version record.
In English.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: African Americans in literature -- History and criticism; American literature -- African American authors -- History and criticism; African Americans -- Race identity -- History; African Americans -- Legal status, laws, etc. -- History; Crime and race -- United States -- History; Citizenship -- United States; Noirs américains dans la littérature -- Histoire et critique; Noirs américains -- Identité ethnique -- Histoire; Criminalité et race -- États-Unis -- Histoire; LITERARY CRITICISM -- American -- African American; African Americans in literature; African Americans -- Legal status, laws, etc; African Americans -- Race identity; American literature -- African American authors; Citizenship; Crime and race; United States; Literatur; Öffentliche Meinung; Schwarze; Ethnizität; Kriminalität; USA; Literatur; Öffentliche Meinung; Schwarze; Ethnizität; Kriminalität; Rasse; Ethnizität; Kriminalität; Bürger; Politische Identität; Kulturelle Identität; USA; American History; American Studies; Cultural Studies; Human Rights; Law; Literature; Criticism, interpretation, etc; History; Criticism, interpretation, etc